Reflections on technology, teaching, learning, and professional development: Findings from a teacher survey in Tanzania - Koomar, Saalim; Hennessy, Sara; Zubairi, Asma; Kindoli, Robert; Kreimeia, Adam (African Educational Research Journal, 2022)
This paper presents findings from a survey of 774 government school teachers across Tanzania over the period 2020-2021. The aims were to capture teachers' recent experiences concerning (1) access and use of technology; (2) any student learning losses observed, and teachers' recommendations to address lost learning; and (3) experiences and needs concerning teacher professional development (TPD). Key findings were (1) forty percent of teachers reported that their school lacked access to any form of technological device, with almost half stating they never used digital technologies for teaching and learning purposes. (2) Almost half of the teachers perceived that girls' learning suffered more than boys, and more than 60% of teachers believed learners from the financially poorest households suffered the greatest learning losses. (3) Teachers in Tanzania engaged in very little TPD and wanted increased support. The key differences across teacher groups were further examined by demographic factors, with notable differences apparent between urban and rural teachers, teachers with different levels of experience and different qualification levels. Recommendations are presented to stakeholders across the education ecosystem, including policymakers, school leaders, TPD designers, teachers, and researchers. The findings inform a national technology-mediated TPD programme in Tanzania.
Publisher: Net Journals ERIC Number: EJ1373064 KerkoCite.ItemAlsoKnownAs: 10.30918/AERJ.104.22.048 10.5281/zenodo.5863400 10.53832/edtechhub.0097 2339240:6EFQH53V 2339240:7QAZINAG 2405685:49EBMKRI 2405685:GXZHRRYW 2405685:YXFLNITE
Keywords: Access to Computers; Elementary School Teachers; Faculty Development; Foreign Countries; Gender Differences; Learning Processes; Pedagogical Content Knowledge; Poverty; Public School Teachers; Rural Urban Differences; Secondary School Teachers; Social Differences; Teacher Attitudes; Teacher Characteristics; Teacher Qualifications; Teacher Surveys; Teaching Experience; Teaching Methods; Technological Literacy; Technology Integration; Technology Uses in Education; _r:AddedByZotZen

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0080 2339240:PRMHXVPE 2405685:7S9CUP77 2405685:HHXQI3S4 2405685:VU5JQKWG 2534378:BXN59IRN
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Tanzanian Teachers’ Experiences of Teaching With Technology: Recommendations for policy and practice - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2022)
This policy brief reports on a teacher survey in Tanzania (July–November 2021) that EdTech Hub commissioned HakiElimu to conduct in order to inform the government’s ongoing national school-based TCPD reform. The survey items were taken from a landmark global survey of 20,000+ teachers’ reflections, experiences, and challenges concerning EdTech access and use, teaching and learning, and professional development over the preceding year, reported by a team from T4 Education and EdTech Hub. Keywords: Educational technology; learning outcomes; teacher needs; teacher professional development; teacher voice; technology access An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6543151 10.53832/edtechhub.0125 2405685:VNE3Q93U
Keywords: _r:AddedByZotZen

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6760137 10.53832/edtechhub.0141 2405685:6VSSZYCK 2405685:KMQCABXM
Keywords: _r:AddedByZotZen

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341501 ZenodoArchiveConcept: 7341500 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341501 10.53832/edtechhub.0138 2405685:E7C9MN3V
Keywords: _r:AddedByZotZen

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech Horizon Scan: Rapid scan on emerging EdTech research during the Covid-19 pandemic. - Ampofo, Rudolph; Kaye, Tom (EdTech Hub, 2022)
EdTech Hub horizon scans are publications designed to provoke thinking and provide insight into a range of topics related to the design, implementation, oversight, and monitoring and evaluation of educational technology (EdTech) tools, products, services, and related ideas. This edition of the Hub’s Horizon Scan provides a high-level summary of research, blogs, and think-pieces published between October and December 2021, that provide insights and learnings on the adoption and utilisation of EdTech during the Covid-19 pandemic. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6959924 10.53832/edtechhub.0107 2405685:UWIQTDFF
Keywords: _r:AddedByZotZen

National EdTech strategies: what, why, and who - Chuang, Rachel; Coflan, Caitlin; Giraldo (UNICEF), Juan-Pablo; Attfield (FCDO), Ian; Tungatarova (UNICEF), Auken; Tungatarova (UNICEF), Caitlin Coflan, Juan-Pablo Giraldo (UNICEF), Ian Attfield (FCDO) and Auken, Rachel Chuang (EdTech Hub, 2022)
Using evidence from Covid responses, the report advises policymakers responding to learning loss caused by the pandemic to use existing EdTech, and focus on good pedagogy that is supported, rather than replaced by, technology.
KerkoCite.ItemAlsoKnownAs: 2339240:G82EPYXB 2405685:MKLN5KM6

National EdTech strategies: what, why, and who - Chuang, Rachel; Coflan, Caitlin; Giraldo (UNICEF), Juan-Pablo; Attfield (FCDO), Ian; Tungatarova (UNICEF), Auken; Tungatarova (UNICEF), Caitlin Coflan, Juan-Pablo Giraldo (UNICEF), Ian Attfield (FCDO) and Auken, Rachel Chuang (EdTech Hub, 2022)
Using evidence from Covid responses, the report advises policymakers responding to learning loss caused by the pandemic to use existing EdTech, and focus on good pedagogy that is supported, rather than replaced by, technology.
KerkoCite.ItemAlsoKnownAs: 2339240:G82EPYXB 2405685:MKLN5KM6